Cochlear implant in Thalassemia patient – Case report. (2nd January 2019) - Kataria, Tanmaya; Grover, Mohnish; Sharma, Shitanshu; Samdani, Sunil; Sharma, Man Prakash
Abstract : Introduction : Beta-thalassemias are a group of hereditary blood disorders characterized by anomalies in the synthesis of the beta chains of hemoglobin. Iron overload occurs in thalassemia, with blood transfusion therapy being the major cause. Deferoxamine continues to be the mainstay of therapy to remove excess iron in patients requiring long-term transfusions. One of the most important complications of deferoxamine therapy is neurosensory toxicity, including sensorineural hearing loss (SNHL). Labyrinthine hemmorhage (LH) is thought to result from altered capillary hemodynamics or reperfusion injury. It is theorized that LH incites a reparative response that cascades from fibrosis to sclerosis and ultimately ossification of the inner ear structures. Case presentation : We present a case of 3-year-old thalassemic child with bilateral profound sensorineural hearing loss. Patient was on regular blood transfusions with chelation therapy. HRCT temporal bone and MRI brain and temporal bone had features of labyrinthitis ossificans (LO). Child underwent uniateral cochlear implantation and postimplantation speech perception and production outcomes were normal. Discussion : This case illustrates the unique feature of labyrinthitis ossificans in a thalassemia patient which has not yet reported in the English literature. Hearing screening of all thalassemia patients and therefore early diagnosis of SNHL prompts early intervention and improved quality of life.